Impact of microRNA polymorphisms on high-dose methotrexate-related hematological toxicities in pediatric acute lymphoblastic leukemia - Zhan, Min; Liu, Ting; Zhang, Zhou; Wang, Guoqiang; Cao, Zhongqiang; Li, Xuejuan; Zeng, Hongwu; Mai, Huirong; Chen, Zebin (Frontiers in Pediatrics, 2023)
Objectives It is well known that transporter and enzyme genes could be regulated by microRNA (miRNA) at the post-transcriptional level, and single-nucleotide polymorphisms (SNPs) in miRNA, which are involved in the miRNA production and structure, may impact the miRNA expression level and then influence drug transport and metabolism. In this study, we aim to evaluate the association between miRNA polymorphisms and high-dose methotrexate (HD-MTX) hematological toxicities in Chinese pediatric patients with acute lymphoblastic leukemia (ALL). Method A total of 181 children with ALL were administered with 654 evaluable cycles of HD-MTX. Their hematological toxicities were evaluated according to the National Cancer Institute Common Terminology Criteria for Adverse Events v5. The association between 15 candidate SNPs of miRNA and hematological toxicities (leukopenia, anemia, and thrombocytopenia) was analyzed using Fisher's exact test. Further multiple backward logistic regression analysis was used to explore the independent risk factors for grade 3/4 hematological toxicities. Result Rs2114358 G>A in pre-hsa-miR-1206 was related to HD-MTX-related grade 3/4 leukopenia after multiple logistic regression [GA + AA vs. GG: odds ratio (OR): 2.308, 95% CI: 1.219–4.372, P = 0.010], and rs56103835 T > C in pre-hsa-mir-323b was associated with HD-MTX-related grade 3/4 anemia (TT + TC vs. CC: OR: 0.360, 95% CI: 0.239–0.541, P = 0.000); none of the SNPs were significantly associated with grade 3/4 thrombocytopenia. Bioinformatics tools predicted that rs2114358 G>A and rs56103835 T>C would impact the secondary structure of pre-miR-1206 and pre-miR-323b, respectively, and then probably influence the expression level of mature miRNAs and their target genes. Conclusion Rs2114358 G>A and rs56103835 T>C polymorphism may potentially influence HD-MTX-related hematological toxicities, which may serve as candidate clinical biomarkers to predict grade 3/4 hematological toxicities in pediatric patients with ALL.